(untitled) (Research, Society and Development, 2023)
This article presents a literature review on the effectiveness of using herbal medicines in the treatment of lupus and other autoimmune diseases. The overall objective of this study is to provide a general and updated understanding of the use of herbal medicines in the treatment of lupus and other autoimmune diseases, analyzing reliable sources and recent advances in the field, in order to contribute to the academic community and provide insights for future research. The topic is justified both to meet the demands of the scientific community in promoting further in-depth research on the relevant subject, and to society as a whole, as it concerns the health of the population. It is a literature review that consulted books, scientific articles, as well as undergraduate theses, also considering foreign literature through searches in electronic databases such as Scielo and Google Scholar, as well as physical library collections. The research results have shown that herbal medicines have been a promising treatment alternative for patients with lupus and other autoimmune diseases, possessing immunomodulatory and anti-inflammatory properties. Furthermore, the review pointed out the need for further research to enhance current knowledge and enrich the discussion on the use of herbal medicines for autoimmune diseases. The final considerations emphasize the importance of continuing research in this area to enhance current knowledge and promote future advances in the therapeutic approach to autoimmune diseases.